Sosialisasi Manfaat Program BPJS Ketenagakerjaan Guna Tingkatkan Kesadaran Tenaga Kerja UMKM di Surabaya - Vynka Zahira Sausan; Lia Nirawati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Based on BPJS Ketenagakerjaan 2019-2021 data, MSMEs, which are businesses in the trade and service sectors, rank 2nd with 142,152 cases of work accidents and occupational diseases (21.4%). The main focus and objective of BPJS Ketenagakerjaan is to provide social protection to workers regardless of the type of work carried out, including workers in the MSME environment. Many people, especially MSME actors, still do not understand about BPJS ketenagakerjaan. It is important for MSME workers to have social security as work protection because Work Accidents and Occupational Diseases can occur at any time while working. This research uses descriptive research with a qualitative approach to describe the implementation of the socialization of the BPJS Ketenagakerjaan program for MSME workers in Surabaya and the methods carried out from socialization activities in the form of observation, interviews, and discussions with the object of research. The purpose of this research is to increase the understanding and awareness of MSME workes of the benefits of the BPJS Ketenagakerjaan program through socialization discussions. The results of this study show that socialization is the best way for BPJS Ketenagakerjaan to provide awareness to the public about the benefits of BPJS Ketenagakerjaan social security programs, especially MSME players in Surabaya. Marketing strategies such as door to door socialization and direct selling have proven to be effective in educating the public and having a positive impact in increasing their participation in the BPJS Ketenagakerjaan social security program